Crescimento, produtividade e trocas gasosas do meloeiro cantaloupe sob doses de nitrogênio e potássio - Fernandes, Leandro Firmino (2013)
Nitrogen and potassium fertilization is the main management technique in the cultivation of melon (Cucumis melo L.), with direct effects on fruit production and quality. In view of the above, the objective was to evaluate the growth and gas exchange in cantaloupe cv. Hy-Mark, under different doses of N and K, grown in full sun. The experiment was conducted in the period from August to November 2015 in a randomized complete block design with 4 replicates. The treatments were constituted by the combination of six levels of N, six levels of K and one control, distributed through Pan Puebla III matrix, forming 11 treatments. N levels were 0; 12; 72; 120; 168 and 228 kg ha-1 and those of potassium corresponded to 0; 18; 108; 180; 252 and 342 kg ha-1, thus the treatments were defined by the following combinations of N and K, respectively: T1 (0;0), T2 (12;18), T3 (12;108), T4 (72;18), T5 (72;108), T6 (72;252), T7 (120;180), T8 (168;108), T9 (168;252), T10 (168;342) e T11 (228;252). The root dry matter (FSR), branches (FSRA), leaves (FSF), root shoot ratio (PA/R), weight sheet ratio (RPF), leaf area ratio (RAF), total leaf area (AFT), Nleaf and Kleaf content and productivity. In the gas exchange analysis, the assimilation rate of CO2 (A), leaf transpiration (E), stomatal conductance (gs) and internal CO2 concentration (Ci) were determined. With these data, the water use efficiency (EUA) and instantaneous carboxylation efficiency (ECi) were determined. Electrolyte extravasation or percentage of relative cell injury (EXTRAVA) was also evaluated. The best dose of nitrogen and potassium for the growth of cantaloupe cv. Hy-Mark, in the field, is between 155 to 183 kg ha-1 of N and 235 to 270 kg ha-1 of K. Nitrogen fertilization has a greater influence on productivity in detriment to potassium fertilization. The best N dose to obtain the maximum productivity should be 227 kg ha-1 of N, in the absence of potassium. The gas exchange in melon cantaloupe cv. Hy-Mark had no effect on the studied N and K doses. Lower doses of N and K promote higher rates of gs, E, Ci and A, while higher doses promote higher rates of EUA and ECi. The extravasation of electrolytes is not potentiated by high doses of N and K. The inverse relation between gs, E and Ci with EUA, characterizes water stress situation.